Modification of Cu/Cr Layered Double Hydroxide by Keggin Type Polyoxometalate as Adsorbent of Malachite Green from Aqueous Solution - Neza Rahayu Palapa; Tarmizi Taher; Alfan Wijaya; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Modification of Cu/Cr layered double hydroxides (LDHs) has been conducted by intercalation using Keggin type polyoxometalate [a-SiW12O40]4- to form CuCr-[a-SiW12O40]. The materials were analyzed by XRD, FTIR, and surface area analyses. Furthermore, materials were used as selectivity adsorbents of cationic dyes such as malachite green, rhodamine-B and methylene blue. The malachite green is more selective than others from an aqueous solution. The adsorption of malachite green showed that the adsorption capacity of CuCr-[a-SiW12O40] was higher than pristine LDHs. The adsorption process was followed pseudo second order kinetic model and Langmuir isotherm adsorption. The Qmax value of CuCr-[a-SiW12O40] reached 55.322 mg/g at 323 K after 100 minutes adsorption time. Thermodynamic parameters such as ΔG, ΔH and ΔS confirm that the adsorption process was endothermic, spontaneous, and more favorable at high temperatures. The intercalated material was higher structural stability toward reusability adsorbent than pristine LDHs.